Statues quo analysis, characterization and assessment of performance of irrigation in Ethiopia - Awulachew, Seleshi Bekele; Yilma, Aster Denekew (2008)
This paper first looks in to the background on major challenges of Ethiopia with respect to poverty. It discuses the root cause of poverty and its vicious cycle nature, the interlink of population growth, the scarcity of land and natural resources, the extension of agriculture in to marginal land, the decreasing productivity, inability to invest and deepening of poverty and further aggravation as a result of various shocks such as drought, flood, war, etc. The paper also looks in to the importance of the broad agricultural water management in general and irrigation in particular with respect to increasing productivity and capability to break the vicious cycle and opportunity to reverse in to virtuous cycle that can help eradicate poverty and develop the poor economy. The paper also looks in to how poor management of water resources and impacts of variability of rainfall and related drought affecting the socio-economy and the overall wellbeing of the country to the extent that significant population became dependent on imported food. Results of broad assessment of water resources, database of irrigation development and potential, characterization by typology and major performance in Ethiopia are presented. Key water resources information related to each of the 12 river basins in Ethiopia is summarized. Details of existing irrigation and future potential are also captured in the paper. A geographic information system (GIS) database describing irrigation by typology, region and location, scheme size, type of structures, water source, number of beneficiaries, investment cost, etc, are some of the important attributes of the database. In addition, schemes that are operational and failed are identified in the database. Based on the broad database, performances of the schemes are highlighted. Furthermore, the various sites that are used in the detail study and the selection criteria for the impact of irrigation on poverty and environment project and the specific characteristics of these sites are described.